Expansion of Shanghai Cooperation Organization (SCO): Implications for Pakistan - Muhammad Ramzan; Amna Mahmood; Manzoor Ahmad Naazer (ASIAN Journal of International Peace & Security (AJIPS), 2021)
Shanghai Cooperation Organization (SCO) is a Eurasian political, economic and security grouping aimed to promote regional peace. In 2017, SCO was expanded and membership was granted to Pakistan and India. Growing status of China, expansion of SCO and its relations with Pakistan has definite implications for Pakistan. The article seeks to analyze the various economic and strategic advantages that Pakistan can achieve through SCO. China-Pakistan Economic Corridor (CEPC) also provides great opportunity to the SCO member states to get fruitful advantages from it. The study employs a qualitative research and descriptive method. The study finds out that SCO is gradually becoming an important organization and more so after the inclusion of two nuclear powers of South Asia, Pakistan and India. Full membership of SCO provides enabling environment to Pakistan to enhance its economic and strategic ties with other member states but at the same time, the other member states would also get advantage from Pakistan’s geographic location for regional connectivity to enhance economic and trade activities.